FEEding DURing red cell transfusion (FEEDUR RCT): a multi-arm randomised controlled trial - Tim Schindler; Kee Thai Yeo; Srinivas Bolisetty; Joanna Michalowski; Alvin Hock Kuan Tan; Kei Lui (BMC, 2020)
Abstract Background Necrotising Enterocolitis (NEC) is a devastating neonatal disease. A temporal association between red cell transfusion and NEC has been recognized and there have been concerns about the effects of feeding during transfusion. We aimed to assess the effect of different enteral feeding regimens on splanchnic oxygenation in preterm infants receiving red cell transfusions. Methods This was an open, multi-arm, parallel-group, randomised controlled trial conducted in a single centre in Australia. We compared three different enteral feeding regimes during a single red cell transfusion in preterm infants < 35 weeks gestational age at birth. Infants were randomised to either: (1) Withholding enteral feeds for 12 h from the start of transfusion or; (2) Continuing enteral feeds or; (3) Restriction of enteral feed volume to 120 ml/kg/day (maximum 20 kcal/30 ml) for 12 h. The primary outcome was mean splanchnic-cerebral oxygenation ratio (SCOR) and mean splanchnic fractional oxygen extraction (FOE) before (1 h prior), during (1 h into transfusion) and after (end of transfusion; 12 and 24 h post) transfusion. Results There were 60 transfusion episodes (20 transfusion episodes in each group) included in the analysis. 41 infants with a median gestational age at birth of 27 weeks (range 23-32 weeks) were enrolled. The median postnatal age was 43 days (range 19-94 days) and the median pre-transfusion haematocrit was 0.27 (range 0.22-0.32). All three groups were similar at baseline. There were no differences in mean SCOR and mean splanchnic FOE at any of the pre-specified time points. There were also no differences in clinical outcomes. There were no episodes of NEC in any infant. Across all groups the mean SCOR increased from the start to the end of each transfusion (0.97 [CI95% 0.96-0.98] vs 1.00 [CI95% 0.99-1.01]; p = 0.04) and the mean FOE decreased from the start to the end of each transfusion (0.22 [CI95% 0.21-0.23] vs 0.17 [CI95% 0.16-0.18]; p < 0.001). Conclusions There were no differences in splanchnic oxygenation when enteral feeds were either withheld, continued or restricted during a transfusion. However, the successful conduct of this study supports the feasibility of a large trial powered to assess clinical outcomes. Trial registration ANZCTR, ACTRN12616000160437. Registered 10 February 2016, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=370069